Local variations in gabion structures. Issue 4 (December 2018) - Clarke, Sam; Barr, Andrew; Warren, Jim; Williams, Angus
Gabion structures are widely used for force protection as they enable locally available material to be used, reducing logistical expense. The soil fill within these structures provides the blast and ballistic resistance; hence, any localised variation in the contained soil can potentially lead to reductions in protective capability. Specifically, built gabion structures were monitored in internal and external environments to assess the variation of soil moisture content and density over a full year and with changing weather conditions. The gabions were filled with fine sand according to manufacturer's instructions. Internal and external moisture content readings were recorded at regular intervals, and a continuously monitoring weather station was installed to collect comparative data. LIDAR scanning was used to record the shape and volume of the gabions to estimate variations in the density of the soil fill. The data indicate that moisture content can vary by over 20% between the top and base of the gabion, and by over 5% from face to face and between readings depending on recent weather conditions, while the core of the gabions remains relatively unaffected. This leads to localised variations in density which can impact on both the ballistic performance and blast resistance of the structure.